Analysis of Dental Caries Risk Factors Based on the DEF-T Index in Children Aged 6-7 Years - Kartini Fajarsari Bilondatu; Margaretha Solang; Cecy Rahma Karim (GLOBAL HEALTH SCIENCE GROUP, 2026)
Dental caries is a chronic disease characterized by the destruction of hard dental tissues, including enamel, dentin, and cementum, resulting from bacterial activity within dental plaque that produces acids from food residues, particularly sugars and carbohydrates, adhering to tooth surfaces. These acids cause enamel demineralization, which, if it progresses, leads to the formation of cavities. This study aimed to analyze the risk factors associated with dental caries occurrence based on the def-t index among children aged 6–7 years in Tolinggula District, North Gorontalo Regency. This cross-sectional study involved 74 children aged 6–7 years selected using purposive sampling. Data were collected through structured questionnaires and clinical examinations, including def-t index assessment and salivary pH measurement. The questionnaire had undergone expert content validation and demonstrated acceptable reliability (Cronbach’s alpha > 0.70). Data were analyzed using the chi-square test and multiple linear regression. The findings revealed significant associations between dental caries occurrence based on the def-t index and the consumption behavior of cariogenic foods and beverages (p = 0.000), toothbrushing frequency (p = 0.000), and salivary pH (p = 0.000). Among these variables, salivary pH was identified as the most dominant factor associated with dental caries occurrence (p = 0.000). Several risk factors were found to be significantly associated with dental caries occurrence based on the def-t index among children aged 6–7 years in Tolinggula District, North Gorontalo Regency, with salivary pH being the strongest contributing factor.